AESTHETIC VALUE IN TITLE IN “HUJAN BULAN JUNI” BY SAPARDI DJOKO DAMONO AND “MALAIKAT JUGA TAHU” BY DEWI LESTARI - Hendrike Priventa (Balai Bahasa Sulawesi Tengah, 2020)
Poetry is a form of literary genre that is full of aesthetic values. The aesthetic value is wrapped in the elements that make up the poetry. This article discusses a comparison of the aesthetic value of the poem “Hujan Bulan Juni” by Sapardi Djoko Damono and “Angels Also Know” by Dewi Lestari. Intertext studies can be used as a medium to find aesthetic values and determine whether literary works are aesthetic or not. The aesthetic value in the poetry